Death in the details: Finding dead bodies at the Canadian War Museum. (July 2017) - Shah, Nisha
Of the 13, 000 works of art in the Canadian War Museum's holdings, only 64 display dead bodies. Prevailing explanations of this absence revolve around respect for the dead and ethical responsibility to avoid the glorification of war. And yet death and destruction are pervasive in war. The irony is that one leaves the museum with the sense that war does not produce corpses, or at least not very many of them. Nowhere is this irony more evident than in the Canadian War Museum's armaments collection, described as 'the way in which human ingenuity has been applied to the science of war, creating weapons and other devices to attack, protect and kill', but with only technical information about weapon calibre and capacities provided. This article describes an effort to dig up the dead. Studying the form and function of the labels accompanying weapons, I argue that seemingly mundane technical specifications classify and standardize certain kinds of bodily injury and death, and make the bodies destroyed by war present. Overall, arguing that injury and death are in the (technical) details, I challenge the assumption that a focus on technological devices sanitizes war. Instead, I propose a way to investigate and interrogate how death and injury in war are calibrated and embodied in the standards that make weapons 'conventional'.